Psychosocial risk predicts high readmission rates for hematopoietic cell transplant recipients. (November 2018) - Richardson, Daniel; Huang, Ying; McGinty, Heather; Elder, Patrick; Newlin, Joanna; Kirkendall, Cyndi; Andritsos, Leslie; Benson, Don; Blum, William; Efebera, Yvonne; Penza, Sam; Hofmeister, Craig; et al.
Abstract Hematopoietic cell transplantation (HCT) is an intensive treatment resulting in disease control however subsequent psychosocial distress is common. Screening for psychosocial risk factors that contribute to morbidity is underutilized; moreover, the value in screening is uncertain. We performed a retrospective study of 395 HCT patients who were screened for psychosocial risk using the Transplant Evaluation Rating Scale (TERS). Patients were classified by psychosocial risk as no-risk (TERS = 26.5, 52%) vs. at-risk (TERS > 26.5, 48%), with at-risk patients stratified by cumulative deficits into mild risk (TERS = 27–35.5, 39%) and moderate risk (TERS > 35.5, 9%). At-risk patients were more likely to be readmitted within 90 days (mild risk HR = 1.62, p  = 0.02; moderate risk HR = 2.50, p  = 0.002). Prior psychiatric history (HR = 1.81, p  = 0.002) and poor coping skills (HR = 1.64, p  = 0.04) also influenced readmission. At-risk patients were more likely to be readmitted for infection (no-risk = 12% vs. at-risk = 25%, p  = 0.002). Pre-HCT screening with the TERS did not predict survival or length of stay although at-risk patients are at a heighted risk of readmission. Implementing strategies to reduce readmission in higher risk patients is warranted.